Silencing of RIPK4 inhibits epithelial-mesenchymal transition by inactivating the Wnt/β-catenin signaling pathway in osteosarcoma - Yi, Zhigang (Mol Med Rep, 2020)
Receptor interacting protein kinase 4 (RIPK4) is a serine/threonine kinase that plays an important role in the regulation of cell proliferation, invasion and metastasis in several malignancies; however, its clinical significance and biological function in osteosarcoma (OS) remains unknown. In the present study, the RIPK4 expression level was significantly upregulated in OS tissues and cell lines. High RIPK4 expression was positively associated with larger sized tumors, advanced Enneking stage and poor prognosis in patients with OS. Furthermore, the results revealed that RIPK4 knockdown in the OS cell lines MG-63 and U2OS reduced cell migration and invasion via the inhibition of epithelial-mesenchymal transition (EMT) process, whereby E-cadherin expression was increased and N-cadherin and vimentin expression decreased. Mechanistically, RIPK4 knockdown inhibited EMT by inactivating the Wnt/β-catenin signaling pathway. These findings suggest that RIPK4 may be a novel potential therapeutic target for the treatment of metastases in patients with OS.